2016
DOI: 10.1530/rep-15-0281
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide enhances apoptosis of corpus luteum in isolated perfused bovine ovaries in vitro

Abstract: Lipopolysaccharide (LPS), the endotoxin of Gram-negative bacteria, has detrimental effects on the structure and function of bovine corpus luteum (CL) in vivo. The objective was to investigate whether these effects were mediated directly by LPS or via LPS-induced release of PGF 2a . Bovine ovaries with a mid-cycle CL were collected immediately after slaughter and isolated perfused for 240 min. After 60 min of equilibration, LPS (0.5 mg/ml) was added to the medium of five ovaries, whereas an additional six ovari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 63 publications
3
29
0
1
Order By: Relevance
“…Binding and activation of TLR4 initiates the production of proinflammatory cytokines and leads to the recruitment of leukocytes . However, in the recent study (Lüttgenau et al 2016) that used isolated perfused ovaries, luteal mRNA expression of TLR4 did not differ between LPS-treated and control ovaries during the first 3 hours after treatment. Apart from the differences in the general approach of the recent and the present study (in vitro vs in vivo), the different outcome in luteal expression of several factors that were investigated in both studies might be due to the different sampling time.…”
Section: Discussionmentioning
confidence: 72%
“…Binding and activation of TLR4 initiates the production of proinflammatory cytokines and leads to the recruitment of leukocytes . However, in the recent study (Lüttgenau et al 2016) that used isolated perfused ovaries, luteal mRNA expression of TLR4 did not differ between LPS-treated and control ovaries during the first 3 hours after treatment. Apart from the differences in the general approach of the recent and the present study (in vitro vs in vivo), the different outcome in luteal expression of several factors that were investigated in both studies might be due to the different sampling time.…”
Section: Discussionmentioning
confidence: 72%
“…We therefore speculated that UPR may be involved in the process of goat luteal cells dividing from follicular granulosa cells and theca cells. The regression of the CL occurs in the late luteal phase of the goat CL and is accompanied with the apoptosis of the luteal cells stimulated by PGF2α ( Tanaka et al, 2000 ; Diaz et al, 2002 ; Luttgenau et al, 2016 ; Kim et al, 2019 ). A previous study revealed that the caspase-dependent apoptosis pathway was significantly activated in bovine CL after PGF2α-injection ( Kliem et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress increases production of proinflammatory cytokines, including tumor necrosis factor α (TNFα) (Chow et al, 1999). Culture of bovine luteal cells in vitro with TNFα increased media concentrations of PGF 2α in a dosedependent manner (Townson and Pate, 1996), and short-term in vitro isolated perfusion culture of bovine ovaries with constant LPS administration increased PGF 2α media concentrations (Lüttgenau et al, 2016b ). Moreover, in vitro culture of porcine luteal tissue after in vivo administration of a PGF 2α analog indicated that luteal tissue itself produced PGF 2α (Diaz et al, 2000).…”
Section: Discussionmentioning
confidence: 99%